2021
DOI: 10.1091/mbc.e21-05-0225
|View full text |Cite
|
Sign up to set email alerts
|

Coilin enhances phosphorylation and stability of DGCR8 and promotes miRNA biogenesis

Abstract: MicroRNAs (miRNAs) are ∼22 nt small noncoding RNAs that control gene expression at the posttranscriptional level through translational inhibition and destabilization of their target mRNAs. The biogenesis of miRNAs involves a series of processing steps beginning with cropping of the primary miRNA transcript by the Microprocessor complex, which is comprised of Drosha and DGCR8. Here we report a novel regulatory interaction between the Microprocessor components and coilin, the Cajal Body (CB) marker protein. Coil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…For the meRIP assay, our qRT-PCR targets were pri-Let7a and pri-miR-21. Pri-Let7a is a miRNA whose biogenesis our lab has found to be regulated by coilin ( Logan et al, 2020 ; Lett et al, 2021 ) and pri-miR-21 is a novel miRNA whose coilin-mediated biogenesis is being investigated for the first time. Both miRNAs have been previously described as being regulated by m 6 A modification ( Konno et al, 2019 ; Ye et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the meRIP assay, our qRT-PCR targets were pri-Let7a and pri-miR-21. Pri-Let7a is a miRNA whose biogenesis our lab has found to be regulated by coilin ( Logan et al, 2020 ; Lett et al, 2021 ) and pri-miR-21 is a novel miRNA whose coilin-mediated biogenesis is being investigated for the first time. Both miRNAs have been previously described as being regulated by m 6 A modification ( Konno et al, 2019 ; Ye et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In wanting to understand how coilin might participate in miRNA biogenesis, our lab has investigated coilin's interaction with the microprocessor complex. To summarize, we have found that coilin suppression reduces DGCR8 phosphorylation and SUMOylation, resulting in decreased protein stability and blunting of microprocessor activity ( Lett et al, 2021 , 2023 ).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…We have previously published that the reduction of proteins enriched in the CB decreases miRNA biogenesis ( Lett et al, 2021 ; Logan et al, 2021 , 2020 ). Importantly, we have also published that coilin reduction in primary cell lines that have few CBs, such as WI-38, also results in decreased miRNA levels, suggesting that coilin contributes to miRNA biogenesis in cells with or without CBs ( Lett et al, 2021 ; Logan et al, 2021 , 2020 ). Therefore, we hypothesize CBs could be an upstream regulator of the miR-517-3p pathway that involves NF-κB and leads to the upregulation of sFlt-1 in hypoxia ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously identified the Cajal bodies (CBs) marker protein, coilin, as a novel regulator of miRNA biogenesis ( Lett et al, 2021 ; Logan et al, 2021 , 2020 ). CBs are phase-separated nuclear condensates that contribute to the biogenesis and maturation of ribonucleoproteins (RNPs).…”
Section: Introductionmentioning
confidence: 99%